Pengaruh Tinggi Air Masuk Dan Diameter Pipa Outlet Terhadap Tinggi Air Keluar Pompa Hidram - Zulhendri Zulhendri; Yuliarman Yuliarman; Menhendry Menhendry; Nota Effiandi; Putri Adeliza (Politeknik Negeri Padang, 2019)
The pump is a device that can lift water from a lower height to a higher place, but because there are many pumps in the market that use electricity as a power plant and the selling price is quite high for rural communities, an appropriate pump is needed and cheap. Hydram pump is one alternative, where the workings of this tool can raise the water to a higher place with energy or power that comes from the water itself. Making Hydram pumps itself is relatively inexpensive, simple and durable. Hydram pumps are very popular because they work without using energy, so it is suitable for use in villages that do not have electricity. The purpose of this study was to determine the effect of the height of the incoming water and the diameter of the outlet pipe on the height of the outlet water at the hydram pump. In this study the height of the incoming water was varied as high as 0.5m, 1m and 1.5m while the diameter of the aoutlaet pipe was varied by 0.5inc, ¾ inc and 1 inc. From this experiment it was found that the height of the incoming water and the diameter of the outlet pipe significantly influence the height of the outgoing water, of the two factors most influential on the height of the outgoing water is the height of the incoming water